Ahmed Arif'in Şiir Anlayışı ve Gelenekle İlişkisi - Aydoğdu, Yusuf (Muş Alparslan Üniversitesi, 2020)
Being one of the important socialist-realistic poets of modern Turkish poetry Ahmet Arif (1927-1991), started to poetry in 1950s and effected many poets who were also socialist-realistic after 1960s. The poet, who collected all of his poems in his work called as Hasretinden Prangalar Eskittim (1968), in spite of writing a few poems, is one of the leading poets having a rare effect. The poet taking his style of poetry, way of saying, discourse and structure of imagery from the traditional richness of Anatolia, in spite of having a socialist identity, has constituted a saying which is not sermonic and sloganic; instead, he has adopted a way of saying which is sincere, spontaneous and original. One of the prominent factors making Ahmet Arif’s poetry different is its relationship with traditions. His adapting the traditional way of saying belonging to Anatolia , especially to the east, to the modern poetry is the biggest indicator of his being familiar with his traditions and his being dependent on lands he lived. In his poetry, from a general aspect, we see the poet tries to keep alive the eastern culture, in a particular sense, he tries to keep alive socio economic reflections of Diyarbakır, cultural forms, folk music, way of talking etc. Folkloric and rhythmic items also feed his poetry. Therefore, sometimes in his poetry we come across with the voice of Dadaloğlu, Pîr Sultan Abdal and Celal Gûzelses who is from Diyarbakir. These folkloric and rhythmic items gains meaning and enriched by the images of socialist poetry.

Modern Türk şiirinin önemli toplumcu-gerçekçi şairlerinden birisi olan Ahmed Arif (1927-1991), şiire 1950’li yıllarda başlamış ve 1960’lardan sonraki birçok toplumcu-gerçekçi şair üzerinde önemli etkiler bırakmıştır. Bütün şiirlerini Hasretinden Prangalar Eskittim (1968) adlı eserinde toplayan şair, çok az sayıda şiir kaleme almasına rağmen, Türk şiirinde örneğine az rastlanır bir etki bırakan şairlerin başında gelmektedir. Şiir iklimini, söyleyiş tarzını ve imgelem yapısını, Anadolu’nun geleneksel birikiminden alan şair, toplumcu bir kimliğe sahip olmasına rağmen sloganik ve vaazcı bir söylemden uzak; içten, doğal, özgün bir şiir dili oluşturmayı başarmıştır. Ahmed Arif’in şiir anlayışını farklı kılan unsurların başında gelenekle kurduğu ilişki gelmektedir. Onun Anadolu’ya özellikle de Doğu Anadolu’ya has geleneksel söylemi modern şiire taşıması, yaşadığı topraklara bağlı, gelenek ve göreneklerine aşina bir şair olduğunun en büyük göstergesidir. Şairin şiirlerinde; genel manada Doğu kültürünü, özelde ise Diyarbakır’ı sosyo-ekonomik yansıması, formları, halk musikisi, konuşma tarzı vb. birçok unsuruyla yaşatmaya çalıştığını görürüz. Bu sebeple onun şiirinde yer yer Dadaloğlu’nun, Pir Sultan Abdal’ın veya Diyarbakırlı sanatçı Celal Güzelses’in sesiyle karşılaşırız. Bu folklorik ve ritmik unsurlar toplumcu şiirin imgeleri ile zenginleşerek özgün bir söyleyiş ve anlam bulur.
Ahmed Arif's Understanding of Poetry and Its Relation with Tradition
anemon
Keywords: Social Loafing; Ahmed Arif; Poetry; Socialist Poetry; Tradition; Discourse; Ahmed Arif; Şiir; Toplumcu Şiir; Gelenek; Söylem